Elementos del costo en la empresa Asycompro S.A.: efectos en la rentabilidad de los períodos 2015-2016. - Torres Torres, Veronica Del Cisne (2017)
The research work is carried out in a commercial entity in the city of Machala, in order to study the elements of cost and its impact on the profitability of the years 2015 and 2016, the company is an organization that is dedicated to the import, export And marketing of inputs and equipment for their food production and in their production uses the raw material, labor and indirect manufacturing costs to offer quality products that have a favorable acceptance in the market, and that has allowed them to get the necessary resources To settle their cash outflows. The elements of production cost (components of the cost of production) are materials, labor and indirect manufacturing costs, these are the components that provide the necessary information for the measurement of income and the price of the product originated This type of study allows managers to have sufficient evidence to establish adequate strategies, policies and decisions in order to guide the company towards a desired economic and financial scenario. Analysis of the costs also allows to know which item is the one that needs the most investment in the accounting period analyzed, a situation that is a measure to determine if this disbursement is adjusted to the results obtained, the structure of the work consists of an introduction where it is given General parameters of the study carried out for a better understanding of the user, is By chapter, where the Chapter I shows the generalities of the object of study, the definition and contextualization macro, meso and micro, then it is observed the fact of interest, where the problems that are the support of the research carried out and which give an alternative Of solution through the suggestions embodied in its pertinent part, in the justification determines the parameters that allow to elaborate the investigation of efficient form and that are fulfilled in the developed practice, in Chapter II presents / displays the theoretical epistemological foundation of the study, The description of the reference approach, the investigative antecedents are related to other investigations with similar characteristics to the one presented, the legal legal basis are the Laws and other Codes and Regulations in which the investigation is framed, starting with the Political Constitution of State as Law Of the Ecuadorian state, in the Chapter II presents the theoretical epistemological basis of the study, the description of the reference approach, the investigative background relate to other investigations with similar characteristics to the presented, the legal legal basis are the Laws and other Codes and Regulations in which it is framed Research, starting with the Political Constitution of State as Law of the Ecuadorian state, Chapter III has the methodological process on which the research is based in order to provide results that are close to the reality of the company and above all that serves as Reference for new research to be developed in the future, then the practice is developed through an appropriate procedure, and finally have the conclusions and recommendations to which the author arrives as a contribution to the efforts undertaken by the administrators of the Company and on the basis of this Followed more closely by their accounting and financial figures in order to improve their current and prospective situation.